Understanding Greek tragic theatre - Rehm, Rush (Milton Park, Abingdon, Oxon Routledge, 2017)
"This book is a revision of Greek Tragic Theatre, originally published in 1992 in the Theatre Production Studies series...."--Preface
A note on translations and editions -- The social and theatrical background -- The performance culture of Athens -- The festival context -- Production as participation -- The theatre of Dionysus -- Conventions of production -- Exemplary plays -- Aeschylus' Oresteia trilogy -- Sophocles' Oedipus Tyrannus -- Euripides' Suppliant women -- Euripides' Ion.
Includes bibliographical references (pages 164-165) and index.
Keywords: Greek drama (Tragedy) -- History and criticism; Political plays, Greek -- History and criticism; Theater -- Greece -- History